Research Capability of Doctoral Students in Utilizing Multivariate Statistics, Writing Research Proposal and Publishable Paper - Caingcoy, Manuel (International Journal of Business, Law, and Education, 2024)
Advanced studies aim to produce highly competent graduates in areas like research and publication. These expectations necessitate research capabilities in graduate students. To assess doctoral students' research abilities and inform instruction, a research course evaluates them at the beginning of the term. Employing a descriptive design, this study investigated 21 individuals enrolled in an advanced research course during the second term of the academic year 2022-2023. Data were collected using an adapted instrument. The results indicated that doctoral students possessed moderate capabilities in writing a research proposal. However, they reported feeling neutral regarding their ability to write publishable papers. Additionally, these individuals indicated a slight or limited capability for utilizing multivariate statistics. These findings hold implications for instruction and future research, particularly in prioritizing course content to address areas where doctoral students have limited research capabilities.